Urinary tract infection in children in a tertiary level hospital in Bangladesh - Islam, MN; Khaleque, MA; Siddika, M; Hossain, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):482-6 The abstract of this article is available on the PubMed website